OPTIMIZATION OF POLYMER INJECTION MOLDING PROCESSES - Yusupov Abdulaziz Abdullajonovich; Yo’ldashev Hayrullo Hasanboy o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This study addresses the optimization of injection molding processes for polymer materials. The main stages of the process, including mold filling, packing under pressure, and cooling, are analyzed. The influence of key process parameters such as melt temperature, mold temperature, injection pressure, and cooling time on product quality and production efficiency is determined. Special attention is given to the improvement of cooling systems, optimization of mold design, and the application of computer-aided engineering (CAE) methods. The proposed approaches enable a reduction in cycle time, minimization of product deformation, and optimization of energy consumption. The obtained results can be applied in industrial practice to improve the quality and productivity of polymer product manufacturing.